Taxation of couples: a mirrleesian approach to collective households - Lima, Lucas Alves Estevam de (2015)
This dissertation presents a alternative approach to deai with family taxation probiem. More specifically we modei lhe family decision as a Nash Bargaining where the pianner can choose optimally lhe disagreement utilities. We prove a Reveiation Principie for this modei so we can consider a smaller set of mechanisms, besides that we compute optimai mechanism gains compareci to other reasonabie mechanism through exampies. We discuss some implications o f lhe optimai mechanism.